Clinical profile of late-preterm infants admitted to a tertiary care hospital - Manerkar, Swati Amol; Kumar, Rajeev; Mondkar, Jayashree (Indian Journal of Child Health, 2018)
Background: Late-preterm babies account for nearly 10% of the total births. Understanding clinical profile of late-preterm infants is important for helping newborn care providers to anticipate and manage potential morbidity during the birth hospitalization and early follow-up. Objective: The objective of this study is to study the clinical profile of late-preterm newborns (340/7 to 366/7 weeks of gestation). Methods: This was a prospective observational study conducted in the neonatal unit of a tertiary care public hospital. All late-preterm babies delivered in the hospital from July 2016 to December 2016, who met the inclusion criteria, were enrolled after taking consent from parents. Detailed antenatal and natal history were noted along with neonatal morbidities and mortality, and the interventions and treatment required by the infants were noted in a structured pro forma. These late-preterm infants were followed up till death/discharge and readmission to hospital and reasons for readmission were evaluated. Results: We enrolled 110 late-preterm babies delivered in our center. The most common morbidity was jaundice requiring phototherapy (63.63%) followed by respiratory distress (24.54%). 25.45% of infants required respiratory support in the form of continuous positive airway pressure or mechanical ventilation. Hypocalcemia and sepsis were observed in 10% of the babies. Feed intolerance was also observed in 16.36% of the babies. The mortality in this group of late preterms was 4.54%. Conclusions: Late-preterm infants show a considerably high rate of medical complications, including need for respiratory support and prolonged hospital stay. Awareness about the neonatal morbidities in late-preterm newborns will facilitate better management of these neonates.